The Effectiveness of Case Method Learning in View of Students' Critical Thinking Ability: Efektivitas Pembelajaran Case Method Ditinjau Dari Kemampuan Berpikir Kritis Mahasiswa - Fauzi, Asri; Ermiana, Ida; Rosyidah, Awal Nur Kholifatur; Sobri, Muhammad (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe the effectiveness of the case method in terms of students' critical thinking skills. This type of research is a quasy experiment with a one-group pretest-posttest design. The population of this study was all students of the Elementary School Teacher Education Study Program (PGSD) at the University of Mataram. The sample used in this study were 29 semesters 2 students taking elementary school mathematics education courses. Data collection techniques using test and non-test techniques. The instrument for collecting data uses a critical thinking ability test. The analysis technique uses the normality test for the prerequisite test, the t-test to find out the difference in the pretest and posttest averages, and the N-Gain score test to determine the effectiveness of the case method. The results showed that the results of the pretest and posttest of students' critical thinking skills obtained successive significance scores of 0.088 > 0.05 and 0.094 > 0.05 meaning that the data was normally distributed. Furthermore, the statistical results of the t-test showed a significance value of 0.000 <0.05. This means that there is a significant difference in average between the pretest and posttest. While the result of the N-Gain score is 0.713 and is in the high category, it can be said that the implementation of the case method has a high level of effectiveness on students' critical thinking skills.